2022
DOI: 10.3233/wor-210752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple risk factors on upper limb musculoskeletal disorders among workers in inner Brazil

Abstract: BACKGROUND: The literature discussing musculoskeletal diseases of inner northeastern workers is scarce, although 67,559 cases were reported in Brazil between 2007 and 2016. OBJECTIVE: This study aimed to evaluate the effect of multiple risk factors that influence the symptoms of work-related musculoskeletal disorders (WMSDs) in wrists, elbows, and shoulders in workers from four different economic sectors. METHODS: A sample included 420 workers from the inner regions of the Brazilian states of Alagoas and Bahia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Furthermore, according to Alias et al [ 58 ], standing for up to 4 h and poor choices of footwear during school hours contribute to symptoms in the feet and lower leg regions. Moreover, Lima da Silva et al [ 69 ] found that jobs in the countryside of northeastern Brazil are precarious and have low wages. Thus, these professionals are often unable to purchase comfortable shoes, only having access to basic necessities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to Alias et al [ 58 ], standing for up to 4 h and poor choices of footwear during school hours contribute to symptoms in the feet and lower leg regions. Moreover, Lima da Silva et al [ 69 ] found that jobs in the countryside of northeastern Brazil are precarious and have low wages. Thus, these professionals are often unable to purchase comfortable shoes, only having access to basic necessities.…”
Section: Discussionmentioning
confidence: 99%